2012
DOI: 10.4025/actascianimsci.v34i4.14471
|View full text |Cite
|
Sign up to set email alerts
|

Time of feed transition and inclusion levels of exogenous protease in rations for piabanha-do-Pardo Brycon sp. hatchery

Abstract: ABSTRACT. Two experiments were conducted which consisted of determining the ideal time to make a feed transition from larvae of 'curimba' Prochilodus hartii to ration (from third, fifth and seventh days of life, with three days of co-feeding), and assess inclusion levels of exogenous protease (0, 0.02 and 0.2%) in the diet of larvae of piabanha-do-Pardo Brycon sp., in a completely randomized experimental design and duration of 15 and 17 days, respectively. Biomass, survival, total length, weight and specific g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…The pH was measured in all treatments varying from a minimum of 6.8 ± 0.01 to a maximum of 7.4 ± 0.02, averaging 7.1 ± 0.17. These results were all within common pH levels for piabanha-do-Pardo pisciculture (Coraspe-Amaral et al, 2012), as well as in fish farming practices for other species of this genus (Pedreira, 2003;Reynalte-Tataje et al, 2004;Pedreira et al, 2006;Pedreira et al, 2008b).…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The pH was measured in all treatments varying from a minimum of 6.8 ± 0.01 to a maximum of 7.4 ± 0.02, averaging 7.1 ± 0.17. These results were all within common pH levels for piabanha-do-Pardo pisciculture (Coraspe-Amaral et al, 2012), as well as in fish farming practices for other species of this genus (Pedreira, 2003;Reynalte-Tataje et al, 2004;Pedreira et al, 2006;Pedreira et al, 2008b).…”
Section: Resultssupporting
confidence: 68%
“…Therefore, this feeding technique has been used in Brycon sp. larviculture (Coraspe-Amaral et al, 2012;Pedreira et al, 2008b). However, further studies testing other live feeding options is necessary to discover new ways to lower production costs, better functionality and produce more positive and constant results (Schütz et al, 2008), other than those observed here.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations